Bridging zero-dimensional loss units with one-dimensional carbon nanotubes for gradient-laminated polyarylene ether nitrile composites toward absorption-enhanced electromagnetic interference shielding - Jiabin Hu; Yunfeng Guo; Yu Zheng; Ting Zhang; Shaoqian Zhou; Yani Chen; Mei Liu; Qian Xiao; Shuning Liu; Xiaobo Liu (Chemical Engineering Journal, 2026)

Microdomain contraction and crystalline refinement in polyarylether nitrile alloys for high-temperature dielectric stability - Ting Zhang; Hongbo Shen; Youbin Wan; Yani Chen; Qian Xiao; Shaoqian Zhou; Yunfeng Guo; Jiabin Hu; Lifen Tong; Shuning Liu; Xiaobo Liu (Chemical Engineering Journal, 2026)

Contribution of dihydroorotate dehydrogenase complex to NADH supply and metabolic flux redirection in Clostridium acetobutylicum - Dandan Jiang; Jihong Yi; Haifeng Zhu; Liangliang Gao; Shuning Wang; Guodong Liu; Lanpeng Li; Quan Zhang; Meng Wang; Armin Ehrenheich; Fuli Li; Yihua Xiao; et al. (Bioresource Technology, 2026)

Measuring and modelling of seed-applied pesticides during soybean emergence - Yang Liu; Xiangshuai Li; Fangkui Zhao; Huizhu Yuan; Xiaojing Yan; Shuning Chen; Daibin Yang (Plant and Soil, 2026)

Directional molecular design of quaternary ammonium deep eutectic solvents: Enabling low-temperature regeneration for CO2 capture - Chao Liu; Boyi Zhang; Shuning Li; Qinghai Long; Xuanang Fu; Huajie Qiu; Huaqiang Fan; Zuoming Zhou; Bihong Lv; Guohua Jing (Chemical Engineering Journal, 2026)

Janus structured magnetic MOFs-polyarylether nitrile/MXene composite films with gradient interfaces for electromagnetic interference shielding and thermal management - Yunfeng Guo; Jiabin Hu; Xin Sun; Ting Zhang; Shaoqian Zhou; Liang He; Hongbo Shen; Lifen Tong; Shuning Liu; Xiaobo Liu (Chemical Engineering Journal, 2026)

Relative quantitative data of cosmetics consumption: An online survey in Guangzhou, China - Junfeng Deng; Zhen Wu; Xiaodan Lu; Xiaoyu Xian; Shixiong Zheng; Yunying Mo; Tianyang Liu; Siyu Sun; Shihan Huang; Ye Hong; Xingyu Yu; Aliya Yijiati; et al. (Regulatory Toxicology and Pharmacology, 2026)

Coarse Woody Debris Maintains Two Distinct and Interrelated Detrital Food Webs in Forest Ecosystems - Zhihui Wang; Yuchen Lu; Shuning Ma; Benjuan Liu; Rui Cao; Lifeng Wang; Yong Zhang; Wanqin Yang (Ecosystems, 2026)

Characteristics of overburden failure and evolution of the water-conducting fracture zone in downward mining of close distance coal seams: a case study of the Shaozhai Coal Mine - Bo Liu; Shuning Dong; Xiaoming Guo; Xinqing Wu; Gang Zheng; Xingling Dong; Lei Liu; Xiyu Zhang (Bulletin of Engineering Geology and the Environment, 2026)

The Training Effect of Tactical Awareness and Technical-Tactical Performance Among Youth Football Players: A Systematic Reviews and Meta-analysis - Jiahui Hu; Yeqin Zhang; Shuning Liu; Danyang Li; Dingmeng Ren (Journal of Science in Sport and Exercise, 2026)

Deep NO oxidation to nitrate with eliminated toxic NO2 by-production via a microwave-constructed Fe–O–C photo-Fenton platform - Jing Guo; Haotong Ma; Zijun Hong; Xuejian Cheng; Chengcheng Ma; Huan Shang; Xinjuan Liu; Yingchun Miao; Shuning Xiao (Journal of Hazardous Materials, 2026)

Improvement of surimi gel quality by lotus leaf and its aqueous extract: Insights from gel properties, digestive characteristics, and functional activities - Meiqi Dang; Shuning Cao; Shikang Sang; Shanbai Xiong; Ru Liu; Tao Yin; Juan You (Food Research International, 2026)

Binding of neonicotinoid compounds to Apis mellifera chemosensory protein 3 (AmelCSP3): Insight into the molecular toxicity of compounds with both risk and potential - Shiyu Li; Xiangshuai Li; Yang Liu; Fangkui Zhao; Daibin Yang; Li Cui; Shuning Chen; Huizhu Yuan; Xiaojing Yan (Pesticide Biochemistry and Physiology, 2025)

Matrix crystallinity and nanofiller compatibility optimization of polyarylether nitrile nanocomposite films for enhanced high-temperature energy storage - Ting Zhang; Yani Chen; Shaoqian Zhou; Jinqi Wu; Yunfeng Guo; Jiabin Hu; Qian Xiao; Lifen Tong; Shuning Liu; Xiaobo Liu (Chemical Engineering Journal, 2025)

Dopamine-functionalized chondroitin sulfate/gelatin-based composite hydrogels for enhancing wound healing and bone regeneration - Jian Yang; Jiale Jin; Haojie Yu; Yun Wang; Li Wang; Xiaowei Liu; Dongyu Wang; Yudi Huang; Chenguang Ouyang; Yu Wang; Yichuan Hong; Shuning Ren; et al. (Carbohydrate Polymers, 2025)

Crop rotation and organic fertilizer maintains diversity and activity of cbbL-carrying CO2-fixing bacteria in reclaimed coal mining soils - Shuning Bai; Meihua Fan; Min Wu; Xiaolong Sui; Yibo Song; Yunlong Jiang; Huisheng Meng; Yulin Liu; Xiangying Wang; Xianjun Hao; Yi Li; Jianping Hong; et al. (European Journal of Soil Biology, 2025)

Corrigendum to “Effects of carboxymethyl chitosan oligosaccharide on regulating immunologic function and inhibiting tumor growth” [Carbohydrate Polymers 250 (2020) 116994] - Zhiwen Jiang; Shuning Wang; Jun Hou; Jinhua Chi; Shuo Wang; Kai Shao; Wanshun Liu; Rongju Sun; Baoqin Han (Carbohydrate Polymers, 2025)

Global environmental footprints of electricity supply in China - Yinchen Liu; Shuning Shi; Kevin J. Gaston; Markus Mueller; Xiaoyu Yan (Journal of Cleaner Production, 2025)

Hierarchical double S-type heterojunction photocatalyst H-ZIF-67-C@NiCo-LDH@Ag2S for enhanced photocatalytic degradation: Reaction pathways, hazard assessment, and mechanistic insights - Xiaofang Feng; Chenchen Liu; Runxuan Long; Xiaobo Liu; Ying Lu; Shuning Liu; Zhongxiang Bai (Journal of Cleaner Production, 2025)

Covalent interface and crosslinked network engineering enable polyarylene ether nitrile nanocomposites with enhanced thermal conductivity and high-temperature energy storage - Shuning Liu; Yani Chen; Jinqi Wu; Ting Zhang; Lifen Tong; Xiaobo Liu (Chemical Engineering Journal, 2025)

Interfacial optimization design and thermal conduction mechanism study of polyarylene ether nitrile composites based on condensed state structure regulation - Lifen Tong; Jinghui Zhang; Liang He; Xiaobo Liu; Shuning Liu (Chemical Engineering Journal, 2025)

High-resolution DNA metabarcoding of modern surface sediments uncovers a diverse assemblage of dinoflagellate cysts in the Pacific and Arctic Oceans - Junyue Wang; Qian Liu; Shuning Huang; Kenneth Neil Mertens; Vera Pospelova; Xin Shen; Haifeng Gu (Marine Pollution Bulletin, 2025)

Initiation mechanism of split grouting cracks at the top of the Ordovician limestone in a coal seam floor - Liu Zhaoxing; Dong Shuning; Zhang Qi; Sun Qiang (Carbonates and Evaporites, 2025)

Keystone ecological cluster rather than the whole community of phoD-encoding bacteria driving ecological function and the improvement of yield under long-term organic regime in greenhouse - Xiaoxia Li; Pengjie Li; Muhammad Awais; Zhu Zhang; Shuning Zhao; Yufeng Liu; Zhouping Sun; Hongdan Fu; Tianlai Li (Agriculture, Ecosystems & Environment, 2025)

Layered double hydroxide-based membranes for advanced water treatment: Structural engineering and multifunctional applications - Yahui Xuan; Xiaofang Feng; Shuning Liu; Xiaobo Liu (Chemical Engineering Journal, 2025)

High-precision permittivity estimation of the Lunar and Mars based on an enhanced approach considering GPR antenna positions - Shuning Liu; Yan Su; Chunyu Ding; Wei Du; Yuhang Liu (Icarus, 2025)

Lanthanide metal–organic frameworks with tunable fluorescence emission for sensing and photonic barcoding - Xiaofang Feng; Shiyong Mou; Yuxuan Pang; Runxuan Long; Chenchen Liu; Zhongxiang Bai; Xiaobo Liu; Shuning Liu (Chemical Engineering Journal, 2025)

Enhanced CO₂ photoreduction to methane via Schottky Zn₃N₂/KPCN heterojunctions for sustainable energy applications - Ziwei Fang; Haotong Ma; Honglei Shao; Wenrui Dai; Zhengyao Qu; Suya Liu; Yuhua Xue; Shuning Xiao (Environmental Research, 2025)

Establishment and application of a duplex fluorescent quantitative PCR assay for H9N2 subtype avian influenza virus and infectious bronchitis virus - Wanting Zhou; Qiuyan Mao; Shuning Zhou; Tingting Li; Jie Tian; Xiaoqi Li; Shuo Liu; Cheng Peng; Zhibin Hu; Jinping Li; Guangyu Hou; Houhui Song; et al. (Virus Genes, 2025)

Analyzing the National Park policymaking process in China from a multiple streams perspective: Domination by the political stream and policy entrepreneurs - Shuning Zhu; Weiye Wang; Jinlong Liu (Forest Policy and Economics, 2024)

Legal challenges of regulating cross-border nuclear pollution from ship ballast water under the background of fukushima wastewater release and China’s response - Xiaofei Liu; Shuning Cao; Yanan Liu (Marine Policy, 2024)

Effect of ozone oxidation on gastrointestinal digestion and absorption characteristics of silver carp (Hypophthalmichthys molitrix) surimi gels in vitro - Shuning Cao; Yuping Pan; Wendong Zheng; Shengjun Chen; Tao Yin; Ru Liu; Juan You (Food Research International, 2024)

How did submarine volcanic eruptions interact with organic matter to favour hydrocarbon generation in the Bohai Bay Basin, China? - Chuanming Li; Jianhui Zeng; Shuning Liu; Yuyang Dong; Maoyun Wang (International Geology Review, 2024)

Adult-type neuronal intranuclear inclusion disease with limb tremor onset: a case report - Shuning Wang; Hui Zhu; Jingyao Liu; Hongping Liu; Hongyu Gao (Acta Neurologica Belgica, 2024)

Study on the decarbonization mechanism of composite adsorbent by Mg-MOF-74-based modified biochar - Chenxing Wang; Li Jia; Shuning Qin; Ling He; Yawen Wu; Qingrui Liu; Yan Jin (Fuel, 2024)

The synergistic nucleation of iodous acid and sulfuric acid: A vital mechanism in polluted marine regions - Haotian Zu; Shaobing Zhang; Shuning Li; Ling Liu; Xiuhui Zhang (Atmospheric Environment, 2024)

Polydopamine-modified magnetic foam composites synergistically activate peroxymonosulfate with visible light for sulfadiazine degradation and oil–water separation - Xiaofang Feng; Chenchen Liu; Runxuan Long; Shuning Liu; Xiaobo Liu (Chemical Engineering Journal, 2023)

Interference of periostin attenuates pathological changes, proinflammatory markers and renal fibrosis in diabetic kidney injury - Xiaoting Duan; Cheng Chen; Xiaoli Liu; Taoxia Wang; Shuning Feng; Jianwei Li; Guiying Li (Genes & Genomics, 2023)

Effects of pea protein isolate on 3D printing performance, nutritional and sensory properties of mango pulp - Shuning Ren; Tian Tang; Xiufang Bi; Xiaocui Liu; Pingkang Xu; Zhenming Che (Food Bioscience, 2023)

Intelligent real-time identification technology of stratum characteristics during slurry TBM tunneling - Yingran Fang; Xinggao Li; Hongzhi Liu; Shuning Hao; Yang Yi; Yidong Guo; Hanyuan Li (Tunnelling and Underground Space Technology, 2023)

Winter-autumn air pollution control plan in North China modified the PM2.5 compositions and sources in Central China - Shuning Jiang; Shaofei Kong; Huang Zheng; Jian Wu; Liquan Yao; Nan Chen; Bo Zhu; Tianliang Zhao; Yongqing Bai; Dantong Liu; Shihua Qi (Atmospheric Environment, 2023)

Unexpectedly significant stabilizing mechanism of iodous acid on iodic acid nucleation under different atmospheric conditions - Ling Liu; Shuning Li; Haotian Zu; Xiuhui Zhang (Science of The Total Environment, 2023)

Identifying influential countries in air pollution control technologies: A social network analysis approach - Shuning Liu; Julien Chevallier; Qingtai Xiao (Journal of Cleaner Production, 2023)

Phthalocyanine-mediated interfacial self-assembly of magnetic graphene nanocomposites toward low-frequency electromagnetic wave absorption - Chenchen Liu; Shuning Liu; Xiaofang Feng; Ke Zhu; Guo Lin; Zhongxiang Bai; Lingling Wang; Xiaobo Liu (Chemical Engineering Journal, 2023)

Evaluating provincial tourism competitiveness in China: an empirical application based on the EM-MGM-SNA model - Ye Tan; Pingan Xiang; Shuning Liu; Liang Yu (Environment, Development and Sustainability, 2023)

Unveiling evolution characteristics of inventive activity on climate change mitigation technologies in China - Shuning Liu; Min Wang; Qingtai Xiao (Environment, Development and Sustainability, 2022)

Identifying spatial relations of industrial carbon emissions among provinces of China: evidence from unsupervised clustering algorithms - Shuning Liu; Chaojun Yang; Liju Liu (Environmental Science and Pollution Research, 2022)

A quadruple recombination event discovered in hepatitis E virus - Hao Shen; Shuning Liu; Min Ding; Haixia Gu; Ming Chang; Yanshuang Li; Hua Wang; Xingwen Bai; Hongxing Shen (Archives of Virology, 2021)

The Water Resisting Properties of the Top Portion of the Ordovician Limestone Aquifer in the North China Coalfield - Hao Wang; Shuning Dong; Rui Chai; Wei Qiao; Jian Yang; Ji Liu; Linsheng Zhou; Zhenfang Zhou; Zhaoxing Liu; Hongbo Shang (Mine Water and the Environment, 2021)

Influences on the performance of cement-based grout used to reform the upper Middle Ordovician limestone in Hanxing mining area - Liu Zhaoxing; Dong Shuning; Wang Hao; Zhao Chunhu; Zhou Zhenfang (Arabian Journal of Geosciences, 2021)

Prevention and Control of Water Inrushes from Subseam Karstic Ordovician Limestone During Coal Mining Above Ultra-thin Aquitards - Xiaolong Li; Shuning Dong; Kaide Liu (Mine Water and the Environment, 2021)

Aeromonas veronii and aerolysin are important for the pathogenesis of motile aeromonad septicemia in cyprinid fish - Chao Ran; Chubin Qin; Mingxu Xie; Jinxiong Zhang; Jie Li; Yadong Xie; Yibing Wang; Shuning Li; Lihui Liu; Xiaozhe Fu; Qiang Lin; Ningqiu Li; et al. (Environmental Microbiology, 2018)
Summary Aeromonas species are ubiquitous inhabitants of freshwater environments, and are responsible for fish motile aeromonad septicemia (MAS). A. hydrophila is implicated as the primary etiologic agent of MAS. Here, we analysed MAS epidemiological data for cyprinid fish in southern China, and found that A. veronii infections dominated. Consistent with this observation, A. veronii isolates were generally more virulent than A. hydrophila isolates when infecting germ‐free zebrafish larvae via continuous immersion challenge. Through in vivo screening of the transposon library of the A. veronii strain Hm091, aerolysin was identified as the key virulence factor. Further results indicated that A. veronii Hm091 aerolysin disrupts the intestinal barrier of zebrafish, enabling systematic invasion by not only A. veronii Hm091 in a mono‐infection, but also A. hydrophila NJ‐1 in a mixed infection. Moreover, the differences in aerolysin expression and activity were the major contributor to the observed differences between the A. veronii and A. hydrophila strains regarding invasion efficacy via intestine. Together, our results provide new insights into the aetiology and pathogenesis of Aeromonas infections, and highlight the importance of A. veronii ‐targeted treatments in future efforts against MAS.

Radiation-Induced Bystander Effects in A549 Cells Exposed to 6 MV X-rays - Shuning Yang; Jing Xu; Weixian Shao; Chong Geng; Jia Li; Feng Guo; Hui Miao; Wenbin Shen; Tao Ye; Yazhou Liu; Haiting Xu; Xuguang Zhang (Cell Biochemistry and Biophysics, 2015)

Instability in mitochondrial membranes in Polima cytoplasmic male sterility of Brassica rapa ssp. chinensis - Ying Li; Tongkun Liu; Weike Duan; Xiaoming Song; Gongjun Shi; Jingyi Zhang; Xiaohui Deng; Shuning Zhang; Xilin Hou (Functional & Integrative Genomics, 2014)

A cDNA Clone of BcHSP81-4 from the Sterility Line (Pol CMS) of Non-heading Chinese Cabbage (Brassica campestris ssp. chinensis) - Tongkun Liu; Xilin Hou; Jingyi Zhang; Yuping Song; Shuning Zhang; Ying Li (Plant Molecular Biology Reporter, 2011)